APLIKASI KONVERSI PIN-READ BCM PADA REGISTRASI INTELLIGEN-KEY KENDARAAN BERBASIS ANDROID - Ahmad Sujana; Artaeza Qomarudin (Jurnal Online Sekolah Tinggi Teknologi Mandala, 2023)
Intelligent-key registration is a process of registering smart remote vehicles so that the vehicle security system is not misused. The application of the conversion of pin-read bcm has been designed to run on android with smart device uses the media app developer inventor. This application made to allow intelligent-key registration were conventional stage in registration in the process. But, using this applications registration intelligent-key so more efficient and effective. Developed with evolutionary prototyping method of development. With a model test in testing and behaviour of testing was definitely blackbox uml. Application that built enough to fulfill its sales target in the sparepart, help when processing intelligent-key registration, and easily used for emergency service.